2020
DOI: 10.3390/ani10050840
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art and Prospective of Nanotechnologies for Smart Reproductive Management of Farm Animals

Abstract: Many biotechnological assisted reproductive techniques (ART) are currently used to control the reproductive processes of farm animals. Nowadays, smart ART that considers technique efficiency, animal welfare, cost efficiency and environmental health are developed. Recently, the nanotechnology revolution has pervaded all scientific fields including the reproduction of farm animals, facilitating certain improvements in this field. Nanotechnology could be used to improve and overcome many technical obstacles that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 52 publications
0
30
0
1
Order By: Relevance
“…Nano-drug delivery systems have been optimized to extend the half-life time of the compound to improve its passage across endothelial or epithelial barriers into blood or lymph circulation and to sustain its delivery to the target sites. Consequently, overcoming these biological barriers can improve cellular uptake and therefore lower doses of drugs/hormones may be used [5][6][7][8][9]. Hence, nano-drug systems for hormonal treatments (e.g., GnRH for ovulation induction) may benefit many biotechnological assisted reproductive techniques in the livestock field (e.g., AI [5]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nano-drug delivery systems have been optimized to extend the half-life time of the compound to improve its passage across endothelial or epithelial barriers into blood or lymph circulation and to sustain its delivery to the target sites. Consequently, overcoming these biological barriers can improve cellular uptake and therefore lower doses of drugs/hormones may be used [5][6][7][8][9]. Hence, nano-drug systems for hormonal treatments (e.g., GnRH for ovulation induction) may benefit many biotechnological assisted reproductive techniques in the livestock field (e.g., AI [5]).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, overcoming these biological barriers can improve cellular uptake and therefore lower doses of drugs/hormones may be used [5][6][7][8][9]. Hence, nano-drug systems for hormonal treatments (e.g., GnRH for ovulation induction) may benefit many biotechnological assisted reproductive techniques in the livestock field (e.g., AI [5]). However, there is a scarcity of data regarding both hormone bioactivity and animal performance when GnRH is used in nano-formula, although previous results are promising.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that NPs express antibacterial activity depending on the size, the concentration and the duration of contact interaction with the target microorganisms [ 59 , 60 ]. It is suggested that exploitation of NPs on animal assisted reproductive management could enhance fertility, considering that different types of NPs produce different effects on semen [ 18 , 61 ]. In our study, Ag/Fe NPs demonstrated higher antimicrobial capacity, along with higher cytotoxicity on ram sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of reactive oxygen species have been identified as possible causes of male infertility ( Dutta et al., 2019 ). These radically active molecules can adversely affect sperm cell motility and sperm DNA integrity, and thus sperm fertilizability ( Hosny et al, 2020 , Hashem and Gonzalez-Bulnes, 2020 ). Similarly, COVID-19 may affect ovum competency through the same oxidative stress pathways ( Menezo et al., 2016 ).…”
Section: Impacts On Assisted Reproductive Technologymentioning
confidence: 99%